(untitled) (IAHS Medical Journal, 2024)
Background: Dacryocystitis is an inflammatory condition of the lacrimal sac, typically caused by obstruction of the nasolacrimal duct. The purpose of the study compares the results of intra operative Mitomycin C application in DCR surgery compared to external DCR without Mitomycin C. Materials and methods: This was randomized control trial. A total of 80 patients of primary acquired nasolacrimal duct obstruction were divided into 2 groups on the basis of simple random sampling. Group-1 contained 40 patients who received 0.02% solution of MMC at the osteotomy site during surgery and considered as the study group and group-2 contained another 40 patients who did not get MMC during surgery and considered as the control group. Patients were followed on 1st post-operative day, 1st week, 1-, 3-, 6- & 12-months interval. Patency of lacrimal passage was assessed by lacrimal syringing and patient’s symptoms were recorded on each follow up. Results: Data shows that there was statistically significant difference in the study showed 39 (97.50%) patients with patent lacrimal passage, only 1 (2.50%) patient was found blocked in their lacrimal drainage system in 1, 3, 6 Months and finally 1 year follow up time. On the other hand in control, 34 (85%) patients showed patency of the drainage system after 1 year and 6 (15%) patients showed blockage and this results was maintained up to 1 year follow up after treatment. During the follow up period, no complications such as abnormal nasal bleeding, mucosal necrosis or infection were noted in any patients. Conclusion: Distinctly higher success rates were achieved in patients undergoing DCR with intra operative MMC as compared to those undergoing external DCR. IAHS Medical Journal Vol 7(1), June 2024; 22-25